Body Mass Index Artistic Gymnastics Athlete in West Java - Sumbara Hambali; Etor Suwandar (JUARA : Jurnal Olahraga, 2019)
The purpose of this study is to find out the body mass index of women's artistic gymnastics in West Java. The research method used is the survey method. The population and sample in this study were all female Javanese artistic gymnastics athletes, amounting to 50 people and sampling using the total sampling technique. The instruments used are BMI (Body Mass Index) with the formula BMI = BB (Kg) / TB (m) 2. The technique of calculating and analyzing data in this study through a quantitative approach in the form of a percentage. Based on the results of the study it can be seen that the average body mass index (BMI) of female artistic gymnastics athletes in West Java is 19.57kg / m2, with a standard deviation of 0.76. Whereas the minimum value is 18.07kg / m2, and the maximum value is 22.06kg / m2. Based on the qualification table of the Body Mass Index (BMI) assessment, it can be concluded that the average female artistic gymnastics in West Java has a qualification for the Normal Body Mass Index.